Strategy For Book Collection Development Policies In Improving Library Services At The Library And Archives Office Of East Kalimantan Province - Andi Anwar; Anwar Alaydrus; Santi Rande (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The purpose of this research is to examine and analyze the Collection Development Policy Strategy in Enhancing Library Services at the East Kalimantan Provincial Library and Archives Office and to understand the factors that support and hinder the Collection Development Policy Strategy in Enhancing Library Services at the East Kalimantan Provincial Library and Archives Office. The method used in this research is a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The research result show findings indicate that the collection development strategy implemented includes regular updating of the collection, diversification of sources of literature (both print and digital), and increased collaboration with publishers and related institutions. Supporting factors for this strategy include leadership commitment, budget availability, and information technology support. However, there are also obstacles such as limited human resources, network constraints, and minimal user involvement in the collection selection process. The conclusion of this research emphasizes that the strategy for development policy Book Collections to Improve Library Services at the East Kalimantan Provincial Library and Archives Service carried out well.